THE EFFECT OF GROUP INVESTIGATION COOPERATIVE LEARNING MODEL ON X CLASS STUDENTS’ CRITICAL THINKING ABILITY ON VIRUS MATERIAL - Wigati, Indah; Fatiqin, Awalul; Permata, Ending (Al 'Ilmi : Jurnal Pendidikan MIPA, 2015)
This research aims to determine the effect of cooperative learning model type Group Investigation (GI) against students critical thinking skills on virus subject in X class. Research Method is quasi experimental design with a pretest-posttest control group design study . Population on research this composed from six class amount 208 students, Sampling on this research used random technique. The sample of research is 66 students. Technique of data collecting with question tests are pretest and posttest . Based on data use results t test on level real 5% for pretest results t arithmetic = 5,556 and t table = 1.998 , then t arithmetic > ttable . Meanwhile, the results of data using t test at the real level of 5% for posttest results t arithmetic = 3,632 and t table = 1.998, then t arithmetic > ttable . This can be seen from the t-test calculation of students critical thinking skills show as sig tarithmetic 0.000 <0,05, then Ha accepted and H 0 rejected . Results analysis calculation per indicator thinking skills students on pretest control class achieved 13.2% very low category while calculations per indicator of critical thinking skills students on pretest experimental class reach 25,3% very low category. The result of calculation analysis per indicator of students critical thinking skill in posttest of control class reach 62,3% low category, while calculation of student critical thinking skill indicator on experimental class posttest reach 82,6% very high category, that is students critical thinking skills more high after application of learning model cooperative type group investigation (GI) . Then could withdrawn conclusion that there the influence of cooperative learning model of Group Investigation (GI) type of students critical thinking on the Virus material of X class.Keywords : learning model, GI, critical thinking, virus